The emergence of the private entrepreneur in reform era China: re-birth of an earlier tradition, or a more recent product of development and change?. Issue 3 (2nd April 2016) - Atherton, Andrew; Newman, Alex
Abstract: A private sector that now dominates economic activity has emerged in China since 1978, even though many of the essential institutions for market competition have been lacking or are under-developed. We find that there is no evidence that this upsurge of entrepreneurship is a re-birth of an earlier tradition. Instead, the dynamics of entrepreneurial emergence can be attributed to reforms and institutional changes that have occurred since 1949, both before and after the introduction of economic reforms in late 1978. We find that these institutional changes have been evolutionary, adapting to, as well as shaping, emerging forms of economic activity, including entrepreneurship. Our conclusion is that these dynamics of adaptation and evolution produce 'rule ambiguities' within the institutional framework that create opportunities for entrepreneurs as well as making these opportunities vulnerable to further institutional change.